Pengaruh Senam Hamil Terhadap Penurunan Nyeri Pinggang Pada Ibu Hamil Trimester III Di Puskesmas Asparaga - Maadi, Astin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: The discomfort of low back pain experienced by pregnant women needs special attention from all parties. Several non-pharmacological techniques that can reduce pain include pregnancy exercises. The aim of this research is to analyze the effect of pregnancy exercise on reducing low back pain in pregnant women in the third trimester at the Asparaga Health Center. Methods: The research method used is experimental qualitative research with a case study approach, by comparing patients before and after being given the intervention. The sample in this study was third trimester pregnant women at the Asparaga Community Health Center, totaling 15 respondents. Results: Based on the results of the study from 15 respondents, 12 respondents (80%) had moderate low back pain and 3 respondents (20%) had mild low back pain. Based on the results of the study from 15 respondents, 6 respondents (40%) had a moderate level of low back pain and 9 respondents (60%) had a mild level of low back pain with statistical results P-Value = 0.000. Conclusion: There is a significant change in the pain scale of 15 respondents which can be seen with a P-Value = 0.000 < 0.05, which means there is a significant effect after carrying out exercise for pregnant women in third trimester pregnant women.